Hyper-Virulent Listeria monocytogenes Strains Associated With Respiratory Infections in Central Italy - Guidi, Fabrizia; Chiaverini, Alexandra; Repetto, Antonella; Lorenzetti, Cinzia; Centorotola, Gabriella; Bazzucchi, Viviana; Palombo, Barbara; Gattuso, Antonietta; Pomilio, Francesco; Blasi, Giuliana (Frontiers in Cellular and Infection Microbiology, 2021)
Listeria monocytogenes (Lm) is a foodborne pathogen causing listeriosis. Invasive forms of the disease mainly manifest as septicaemia, meningitis and maternal-neonatal infections. Lm-associated respiratory infections are very rare and little known. We reported two Lm respiratory infection cases occurred in Central Italy during the summer of 2020, in the midst of the SARS-CoV2 pandemic. In addition to collect the epidemiological and clinical characteristics of the patients, we used Whole Genome Sequencing to study the genomes of the Lm isolates investigating their virulence and antimicrobial profiles and the presence of genetic mobile elements. Both the strains belonged to hypervirulent MLST clonal complex (CC). In addition to the Listeria Pathogenicity Island 1 (LIPI-1), the CC1 strain also carried LIPI-3 and the CC4 both LIPI-3 and LIPI-4. Genetic determinants for antimicrobial and disinfectants resistance were found. The CC1 genome presented prophage sequences but they did not interrupt the comK gene, involved in the phagosomal escape of Lm. None of the strains carried plasmids. Lm is an important, although rare, opportunistic pathogen for respiratory tract and lung infections. It is important to consider this possible manifestation of listeriosis to avoid dangerous diagnostic delays and promptly intervene with drug treatment of these severe clinical forms of the disease.